Tumor Repression of VCaP Xenografts by a Pyrrole-Imidazole Polyamide - Hargrove, Amanda E.; Martinez, Thomas F.; Hare, Alissa A.; Kurmis, Alexis A.; Phillips, John W.; Sud, Sudha; Pienta, Kenneth J; Dervan, Peter B. (PLOS ONE, 2015)
Pyrrole-imidazole (Py-Im) polyamides are high affinity DNA-binding small molecules that can inhibit protein-DNA interactions. In VCaP cells, a human prostate cancer cell line overexpressing both AR and the TMPRSS2-ERG gene fusion, an androgen response element (ARE)-targeted Py-Im polyamide significantly downregulates AR driven gene expression. Polyamide exposure to VCaP cells reduced proliferation without causing DNA damage. Py-Im polyamide treatment also reduced tumor growth in a VCaP mouse xenograft model. In addition to the effects on AR regulated transcription, RNA-seq analysis revealed inhibition of topoisomerase-DNA binding as a potential mechanism that contributes to the antitumor effects of polyamides in cell culture and in xenografts. These studies support the therapeutic potential of Py-Im polyamides to target multiple aspects of transcriptional regulation in prostate cancers without genotoxic stress.